Housing, health and social care – an introduction. Issue 1 (2014) - ,
Abstract : Purpose – There are clear links between health, housing and social care. The homeless live much shorter lives as do those people living in poorer quality accommodation and areas of deprivation. Life expectancy and the quality of life in later years are both drastically affected by Marmot's (2010) social gradient, with people from poorer backgrounds often doing worse. A decent home is fundamental to a healthy and a good life. The paper aims to discuss these issues.Design/methodology/approach – The research approach reviewed existing articles, examples from the housing sector and analysis of a range of data from organisations including the NHS.Findings – Good housing helps to support better health but it is not the only answer – joined up working between agencies and Marmot's proposal of proportionate universalism are significant factors in finding solutions to this long‐standing issue.Social implications – Costs to the government, health services and local authorities and other agencies could be reduced by wider thinking around the link between housing, health and other support.Originality/value – This paper focuses on the existing links between health, housing and social care.